2002
DOI: 10.1111/1468-2338.00225
|View full text |Cite
|
Sign up to set email alerts
|

Worker representation in health and safety: options for regulatory reform

Abstract: Worker representation in health and safety in Britain hasreceived statutory support since the Safety Representatives and Safety Committees Regulations 1977. Subsequent developments have, however, acted to undermine the effectiveness of these regulations. The paper consequently discusses a range of reforms that could be introduced to strengthen the present regulatory regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
5

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 9 publications
1
33
0
5
Order By: Relevance
“…The resulting legislation, however, adopted a more balanced approach believing that the standard of protection afforded to workers would be higher where employees, through their representatives, had a more significant voice and involvement in the consultative process (James and Walters, 2002). Thus in union-recognized firms, and these only, trade unions were able to appoint OHS representatives who could call for the establishment of health and safety committees, investigate potential hazards and complaints and have paid leave to carry out these tasks (as amended by the Safety Representatives and Safety Committees Regulations [SRSC] 1977).…”
Section: Introductionmentioning
confidence: 99%
“…The resulting legislation, however, adopted a more balanced approach believing that the standard of protection afforded to workers would be higher where employees, through their representatives, had a more significant voice and involvement in the consultative process (James and Walters, 2002). Thus in union-recognized firms, and these only, trade unions were able to appoint OHS representatives who could call for the establishment of health and safety committees, investigate potential hazards and complaints and have paid leave to carry out these tasks (as amended by the Safety Representatives and Safety Committees Regulations [SRSC] 1977).…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, several studies have confirmed the argument that the most effective health and safety committees are those for which both employee representatives and management have been trained and in which representation operates through established trade-union channels (James & Walters, 2002;Walters, 1996). Reilly, Paci, and Holl (1995) showed that injury rates tend to be highest in workplaces where there is a unilateral determination of health and safety by management, and lowest where mechanisms of unionbased representation are present.…”
Section: Contrasting Industrial Relations Systemsmentioning
confidence: 99%
“…In the specific context of health and safety, research evidence shows that the safest workplaces are those workplaces that have strong trade union representation (James and Walters ; Walters et al . ).…”
Section: Policing the Building Sitementioning
confidence: 99%